Association of structural uterine defects with repeated pregnancy loss: hysteroscopic assessment (BIRDEM Medical Journal, 2025)
Background: Recurrent pregnancy loss (RPL) is defined as the loss of two or more pregnancies. Structural uterine defects (SUD) are often associated with RPL which can be either congenital or acquired. Hysteroscopy is the gold-standard method for evaluation of SUD. The objective of this study was to evaluate the prevalence of SUD among Bangladeshi women with RPL based on hysteroscopic findings. Methods: This cross-sectional study was conducted at Farida Clinic and Infertility Management Center from January 2021 to December 2023. In total of seventy-six women who underwent hysteroscopic assessment for two or more consecutive miscarriages were included in the study. Results: Majority (n=36, 47.4%) of the women belonged to age group 31-35 years with mean age of 31.75 years. Sixty-two women had repeated miscarriages in first trimester (81.6%) and 14 (18.4%) in second trimester of pregnancy. On hysteroscopy, abnormal uterine cavity was found in 30 (39.5%) and normal cavity was in 46 (60.5%) patients. Congenital structural defects (n=24) were mostly septate or sub-septate uterus (n=11) followed by bicornuate uterus (n=8). Among the acquired structural anomalies (n=16), polyps were the commonest (n=8) followed equally by fibroids (n=4) and synechea (n=4). No significant association (P=0.390ns) was found between timing and number of miscarriages with endometrial cavity abnormality. Conclusions: The result of our study suggests that nearly 40% had SUD and timing and number of miscarriages in RPL did not correlate with the different types of SUD on hysteroscopy.BIRDEM Med J 2025; 15(2): 63-68